Toleration and Persecution in colonial Natal - Brain, Joy B. (Studies in church history, 1984)
Natal was the second acquisition of the British Empire in Southern Africa. While the Cape Colony was acquired permanently in 1814, and the Orange River Sovereignty temporarily in 1848 only to be abandoned in 1854, Natal was annexed reluctantly but permanently, for mixed strategic and philanthropic reasons, in 1844. The White population at this time was a few thousand, the Black about eighty thousand. The only missionary work that had taken place up to this time was that of the American Board of Commissioners for Foreign Missions, which had established two stations in Zululand in 1835, and the Church Missionary Society. In the period before the annexation they had had little success among the Zulus in Natal, and none at all in Zululand because of Dingane’s attitude to them. All left Zululand in 1838 and the missions were not reopened until the 1860s.